Literature Study: Development of Augmented Reality-Based Early Childhood Education Learning Media (Current Research in Education: Conference Series Journal, 2024)
In the era of the Industrial Revolution 4.0, technology plays an important role in various aspects of life, including education. One technological innovation that can be applied in early childhood education is Augmented Reality (AR). This study aims to (1) determine the urgency of using AR technology in early childhood learning media; (2) explain the process of integrating AR technology into learning media; and (3) identify the effects of AR-based learning media on early childhood development. The research method used is a literature study by collecting, analyzing, and concluding findings from previous studies related to AR in education. The results show that (1) the use of AR is essential to introduce children to technology from an early age, preparing them to adapt and compete in the Industrial 4.0 era; (2) AR integration can be implemented through various learning materials, such as introducing numbers, letters, and creating interactive “Magic Book” media; and (3) the use of AR-based learning media has been proven to increase children’s learning motivation, curiosity, and activeness. Therefore, it is recommended that early childhood education institutions in Indonesia begin adopting AR technology to make learning more interactive, engaging, and relevant to current technological developments.